Alan Moore and the Migrating Art of Comics. Nicoletta Vallorani interviews Annalisa Di Liddo (Altre Modernità, 2009)
Alan Moore and the Migrating Art of Comics.  Nicoletta Vallorani interviews Annalisa Di Liddo